La demanda de salud infantil en el Perú: un análisis teórico y empírico - Cortez, Rafael (1995)
The author delves into the factors influencing health services demand. An empirical analysis was conducted based on regression models with dichotomous variables on a sample group of 4,540 children. The main questions the piece attempts to answer are: Which are the factors behind the frequency of child illness in Peru and the household leader's decision to seek the assistance of medical services?; and what dictates the decision to visit a specific health center.